RHEUMATIC MANIFESTATIONS IN VIRAL HEPATITIS - L P Anan'eva; L P Ananyeva (Современная ревматология, 2008)
Autoimmune reactions are of primary importance in the development of extrahepatic manifestations of viral hepatitis, among which there are rheumatic symptoms and syndromes. The incidence of clinically significant extrahepatic manifestations is shown to be relatively low, but they may be in the foreground in the clinical picture of the disease and are noted for severity. It is concluded that due to the high prevalence of hepatitis and the systemic pattern of their chronic forms, patients with extrahepatic manifestations of viral hepatitis may be encountered in the practice of a therapist and a rheumatologist. The onset of the infection caused by hepatitis viruses may be accompanied by articular lesion therefore the rheumatologist may be the first physician such a patient may resort to.